If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 = 60 + -2p Solving 20 = 60 + -2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2p' to each side of the equation. 20 + 2p = 60 + -2p + 2p Combine like terms: -2p + 2p = 0 20 + 2p = 60 + 0 20 + 2p = 60 Add '-20' to each side of the equation. 20 + -20 + 2p = 60 + -20 Combine like terms: 20 + -20 = 0 0 + 2p = 60 + -20 2p = 60 + -20 Combine like terms: 60 + -20 = 40 2p = 40 Divide each side by '2'. p = 20 Simplifying p = 20
| 8x^2-24x-1440= | | 3x^2+84x+588= | | 36x^5+121x=0 | | 5x^2+70x+245= | | x^(-2)=4/9 | | 0.6(x+200)=0.66x-336 | | (x/4)=(3x/5)-(9-x/10) | | 12y+6xy= | | 2x-3y-z=0 | | 3(x+7)=-2(x-9) | | 2x+13+173x=180 | | 2x-3y=-z | | 3x+4y+5z=180 | | 12(5x-2)=48+12x | | 6+4(3x-6)=8-4(2x+1) | | 0.6(x+200)=0.66x-366 | | 15x-8=40x+12 | | 0.50x+0.35(30)=45.5 | | 5a^4b-(5a^2b^2)=x | | 15b-35=5b+18 | | 15(8x-24)=120 | | 5(x-3)=x+6 | | X-5/3-5=x-7/2 | | 5+35x=20x+23 | | 4-12x+9x^2= | | 2x^2-64x+512= | | 8x/9-1=39 | | 10(z+4)-3(z-3)=3(z-3)+3(z-3) | | 5(2x-9)-3=5(x-4)+2 | | 5x-51=4x-68 | | 13x-(8x-2)=37 | | 5x+5=-65-5x |